Surface Charge Transfer Doping of Low-Dimensional Nanostructures toward High-Performance Nanodevices - Zhang, Xiujuan; Shao, Zhibin; Zhang, Xiaohong; He, Yuanyuan; Jie, Jiansheng (Advanced materials (Weinheim), 2016)
Device applications of low‐dimensional semiconductor nanostructures rely on the ability to rationally tune their electronic properties. However, the conventional doping method by introducing impurities into the nanostructures suffers from the low efficiency, poor reliability, and damage to the host lattices. Alternatively, surface charge transfer doping (SCTD) is emerging as a simple yet efficient technique to achieve reliable doping in a nondestructive manner, which can modulate the carrier concentration by injecting or extracting the carrier charges between the surface dopant and semiconductor due to the work‐function difference. SCTD is particularly useful for low‐dimensional nanostructures that possess high surface area and single‐crystalline structure. The high reproducibility, as well as the high spatial selectivity, makes SCTD a promising technique to construct high‐performance nanodevices based on low‐dimensional nanostructures. Here, recent advances of SCTD are summarized systematically and critically, focusing on its potential applications in one‐ and two‐dimensional nanostructures. Mechanisms as well as characterization techniques for the surface charge transfer are analyzed. We also highlight the progress in the construction of novel nanoelectronic and nano‐optoelectronic devices via SCTD. Finally, the challenges and future research opportunities of the SCTD method are prospected. Surface charge transfer doping (SCTD) is emerging as a simple yet efficient technique to achieve reliable doping in low‐dimensional nanostructures in a nondestructive manner. The recent advances of SCTD in one‐ and two‐dimensional nanostructures are summarized systematically and critically. Progress in the construction of novel nanoelectronic and nano‐optoelectronic devices via SCTD is also highlighted.